Audio-Based Music Structure Analysis: Current Trends, Open Challenges, and Applications - Nieto, Oriol; Mysore, Gautham J.; Wang, Cheng-i; Smith, Jordan B. L.; Schlüter, Jan; Grill, Thomas; McFee, Brian (Transactions of the International Society for Music Information Retrieval, 2020)
With recent advances in the field of music informatics, approaches to audio-based music structural analysis have matured considerably, allowing researchers to reassess the challenges posed by the task, and reimagine potential applications. We review the latest breakthroughs on this topic and discuss the challenges that may arise when applying these techniques in real-world applications. Specifically, we argue that it could be beneficial for these systems to be application-dependent in order to increase their usability. Moreover, in certain scenarios, a user may wish to decide which version of a structure to use, calling for systems with multiple outputs, or where the output adapts in a user-dependent fashion. In reviewing the state of the art and discussing the current challenges on this timely topic, we highlight the subjectivity, ambiguity, and hierarchical nature of musical structure as essential factors to address in future work.